Precision mass measurements of cesium isotopes—new entries in the ISOLTRAP chronicles. (23rd February 2017) - Atanasov, D; Beck, D; Blaum, K; Borgmann, Ch; Cakirli, R B; Eronen, T; George, S; Herfurth, F; Herlert, A; Kowalska, M; Kreim, S; Litvinov, Yu A; et al.
Abstract: Alkali ion beams are among the most intense produced by the ISOLDE facility. These were the first to be studied by the ISOLTRAP mass spectrometer and ever since, new measurements have been regularly reported. Recently the masses of very neutron-rich and short-lived cesium isotopes were determined at ISOLTRAP. The isotope 148 Cs was measured directly for the first time by Penning-trap mass spectrometry. Using the new results, the trend of two-neutron separation energies in the cesium isotopic chain is revealed to be smooth and gradually decreasing, similar to the ones of the barium and xenon isotopic chains. Predictions of selected microscopic models are employed for a discussion of the experimental data in the region.